Clinical comparison of single-oral-dose cefuroxime axetil and amoxicillin with probenecid for uncomplicated gonococcal infections in women. - Baddour, L M (1989)
Four hundred sixty-six female patients were enrolled in a randomized study that compared the clinical efficacies of single oral doses of cefuroxime axetil and amoxicillin with probenecid in the treatment of uncomplicated gonorrhea. Two hundred ninety-five patients had culture-positive gonococcal infections and completed the investigation. Cure rates for the patients treated with cefuroxime axetil and those treated with amoxicillin with probenecid were high (greater than 95%) for genitorectal infections. Pharyngeal infections, however, were not uniformly eradicated by either cefuroxime axetil (60%) or amoxicillin with probenecid (64%). Approximately 13% of each patient group suffered adverse events, which were gastrointestinal in the majority and were transient. Compared with amoxicillin plus probenecid, cefuroxime axetil in a single oral dose was an equally safe and effective drug for the treatment of uncomplicated gonorrhea in women caused by penicillin-susceptible strains.